Mainstreaming climate adaptation in spatial planning: the case of Baixa Pombalina in Lisbon - Ribeiro,Patrícia (2018)
Baixa Pombalina is the historical downtown area of Lisbon city, close to the Tagus estuary, accommodating many economic activities namely tourism. This paper assesses and maps the vulnerability of the area, at the neighbourhood scale, to flood episodes and sea level rise. The methodology outlines how the different components of vulnerability are tackled, while considering the importance of the local context in the definition of composite indexes. Twenty-two vulnerability hotspots were found, for which six adaptation options are proposed to be embedded into the Plano de Pormenor currently in place.